CONCEPTUAL FOUNDATIONS OF THE DEVELOPMENT OF DIGITAL COMPETENCE OF THE WORKFORCE OF UKRAINE - SHATALOVA, L.S. (Economic innovations, 2023)
Topicality. The key role of digital competence is related to meeting the needs of the Fourth Industrial Revolution, the driver of which is digitalization, which has become the main imperative of modernity. The comprehensive and dynamic nature of digital transformation causes changes in most spheres of life in society, which force people to quickly adapt to them. In such conditions, increasing the competence potential of labor resources in terms of digital competence becomes a necessary condition for the successful functioning of not only individuals and society, but also the socio-economic system in general. Digital competence is becoming transversal, which is recorded in many international documents, in particular the Framework Program of the renewed Key competences for lifelong learning of the European Parliament and the Council of the European Union and the report "Towards a structured and agreed terminology of cross-cutting skills and competences" of the European Commission and the European Center for the development of vocational training. The European vector of development and the complexity of the socio-ecological and economic environment of Ukraine determine the need to build an individual trajectory of digital education of the population based on the study and implementation of the experience of the European Union in the specified field of activity.Aim and tasks. The purpose of the article is to develop the conceptual foundations of the development of the digital competence of the workforce of Ukraine.Materials and methods. The information sources of the research are fundamental and applied research by domestic and foreign scientists on issues of competence potential in terms of digital literacy, as well as leading international organizations, in particular, the European Center for the Development of Professional Education, the European Commission, UNESCO, data from open sources. To achieve the goal, the methods of system analysis, logical generalization and content analysis were used.Research results. The role and significance of digital competence in the context of modern socio-economic development is considered. The concept of "digital competence" was studied from the point of view of essential content and officially defined interpretations. It is proposed to determine the levels of digital competence in economic activity in terms of the structure of business processes and the level of knowledge-intensive production on the basis of the European approach to determining the level of qualifications presented in DigComp2.1, according to which it is proposed to use depending on the complexity and level of autonomy of task performance, as well as the type cognitive operations (memorizing, understanding, applying, evaluating, creating) 4 levels of qualification: foundation, intermediate, advanced and higly specialised. It is outlined that the prospects for further research are related to the study of the criteria for determining the levels of digital competence in terms of structure-forming business processes, which will contribute to the effective use of the labor potential of the population of Ukraine.Conclusion. In the conditions of the digital transformation of the economy, digital competence acquires a transversal character, since almost all professions will have a digital component in the future. In turn, the formation, application and development of digital competence of the population in terms of different categories is a complex and long-term process that requires coordination and synchronization in time of various interdependent components, in particular, regulatory and legal, institutional, material and technological and personnel, each of which needs to solve a complex of problems. It is important to understand that in order to effectively use the labor potential and increase labor productivity, it is necessary to maintain the correspondence of the qualification level of the digital competence of the workforce to the complexity of the tasks, depending on the scientific intensity of the production processes.